Jelajah Pemikiran Josef Prijotomo terhadap Arsitektur Nusantara (Tahun 1999-2020): Kajian Sejarah Pemikiran - Linda Octavia (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2021)
Title: Exploration on Josef Prijotomo Thinking towards Nusantara Architecture (1999-2020): A History of Thought Studies The Indonesian historical journey in which showing the traces of architectural discourse is still on its way. One of the strong discourses in forming the foundation of thinking is Nusantara Architecture. Nusantara Architecture, as suggested by Prijotomo, is an architecture in which its perspective, concepts, and theories are developed based on Mother Nature. Prijotomo has been working in the formation of this Thinking and it evolves in time. It is important to understand this journey as well as to understand Nusantara Architecture The study of the exploration of Prijotomo’s thinking about Nusantara Architecture (1999-2020) aims to identify the shift of Prijotomo’s way of thinking from Traditional Architecture to Nusantara Architecture, as well as identifying the impacts or implications of Prijotomo’s thinking in the recent era. The study uses a historical research method using documents and oral sources. The document sources used are the original ones including books and articles written by Prijotomo within 1999-2020, while the oral sources are the direct conversation with Prijotomo. Through the exploration, it can be concluded that using Nusantara Architecture thinking, Prijotomo has attempted to make the base thought of Mother Nature equal to Western Architecture (European and American). This study serves as a starter to place Nusantara Architecture as architectural knowledge that is ‘liyan (the other)’ in relation to Western Architecture (European and American). The thoughts in seeking the base foundations for architects of (in) Indonesia are still ongoing. However, the offer and even the basis initiated and proposed in a series of Prijotomo’s deep thinking struggle are crucial and relevant. Emendation and purification by Prijotomo should be used and sustained by the various Architecture stakeholders in Indonesia.